Peran Media Digital dalam Meningkatkan Kemampuan Berbicara Siswa pada Pembelajaran Bahasa Arab - Dedeh Sya'adatul Kamilah; Nurhaliza Naelatul Minhah (Lembaga Penelitian dan Pengabdian kepada Masyarakat(LPPM), STAI PUI Majalengka, 2026)
The development of digital technology has brought significant advancements to the Arabic language learning process, particularly in the development of speaking skills (maharah kalam). This study aims to examine the role of digital media in improving students' maharah kalam skills in Arabic language learning. The research employed a library research method with a descriptive qualitative approach. Data were collected through the review of relevant scientific literature, including journal articles, books, and academic publications discussing the use of digital media in Arabic language learning published between 2019 and 2025. Data analysis was conducted using content analysis techniques, which involved the processes of identification, classification, interpretation, and synthesis of data. The findings reveal that digital media plays a crucial role in enhancing students' maharah kalam skills by creating a more interactive, flexible, and communicative learning environment. Various forms of digital media utilized in the learning process include vlogs, interactive videos, social media, Learning.Aljazeera.Net, Alef Education, and other digital learning platforms. The use of digital media has been proven to improve students' learning motivation, self-confidence, vocabulary mastery, pronunciation, and active participation in Arabic language learning. However, the implementation of digital media also faces several challenges, such as limited access to technology, internet connectivity issues, and teachers' digital competencies. Therefore, adequate facilities and infrastructure, as well as continuous professional development for teachers, are essential to optimize the use of digital media in maharah kalam learning.